Employing e-learning tools and resource materials in the successful implementation of competency-based medical education in India - Shrivastava, Saurabh; Shrivastava, Prateek (Medical Journal of Babylon, 2023)
Competency-based medical education (CBME) has emerged as one of the modes of the curriculum which is built around a framework of competencies and plays an important role in the making of a healthcare professional who is competent enough to meet the health care needs of the society. The purpose of the current review was to explore the role of e-learning in enhancing learning in different domains of learning and identify the various e-learning resources. An extensive search of all materials related to the topic was carried out on the PubMed search engine and a total of 35 articles were selected based upon the suitability with the current review objectives and analyzed. The search was carried out for a period of one month and all articles published between 2003 to 2021 were included. As only one search engine was used, there were no duplications. Keywords used in the search include e-learning and medical education in the title alone only. E-learning has been acknowledged as one of the significant curricular reforms, which has the potential to bring about a paradigm shift in medical education in India. The basic rationale for the utility of e-learning in the medical curriculum originates from the fact that the syllabus is extremely vast and students have to study many subjects in a fully-packed schedule, and that cannot happen only within the classroom hours. E-learning can play an important role in the augmentation of cognitive, psychomotor, and attitudinal/communication skills through the optimal use of e-learning resources. To conclude, e-learning has emerged as an important approach to strengthen the process of implementation of competency-based medical education in Indian settings. The need of the hour is to acknowledge the merits of e-learning and plan strategies for the successful integration so that the overall process of CBME implementation can be strengthened and streamlined.